2013
DOI: 10.4018/irmj.2013070102
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Needs, Capabilities and Decision Making Mechanisms in Digital Preservation

Abstract: Firms are required to consciously retain information in an effort to ensure compliance with legal and business needs. However, sustained accessibility to digital information cannot be taken for granted as it is threatened by expeditiously changing technologies associated with the risk of obsolete soft- and hardware. As part of an effort to ensure long-term access to digital information, digital preservation (DP) provides effective means. But still little is known about DP in firms. In this study the authors ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Despite having greater explanatory power, limited studies have used this model in cloud computing studies (San-Martín & Herrero, 2012;Cao et al, 2013). In the past, researchers have largely used TAM or DOI model to understanding cloud technology adoption (Langkau et al, 2012;Gupta et al, 2013;Burda & Teuteberg, 2014;Udo et al, 2016).…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut) Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having greater explanatory power, limited studies have used this model in cloud computing studies (San-Martín & Herrero, 2012;Cao et al, 2013). In the past, researchers have largely used TAM or DOI model to understanding cloud technology adoption (Langkau et al, 2012;Gupta et al, 2013;Burda & Teuteberg, 2014;Udo et al, 2016).…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut) Mmentioning
confidence: 99%
“…The second construct in UTAUT model is Effort expectancy and it is similar to perceived ease of use in TAM (Venkatesh et al, 2003;Min et al, 2008). Several research studies (Wu, 2011;Gupta et al, 2013;Burda & Teuteberg, 2014;Lian 2015) have found that there is strong influence of perceived ease of use on the behavioral intention to adopt cloud computing services. Thus, it is posited that: H2: Effort expectancy has a positive effect on users' behavioral intention to use cloud computing services.…”
Section: Proposed Research Model and Hypothesis Formulationmentioning
confidence: 99%